Eksistensi Putusan Mahkamah Konstitusi - Fatriansyah, Fatriansyah (Legalitas: Jurnal Hukum, 2023)
The Constitution has stipulated that the Indonesian state is a state of law, the implementation of which is carried out by the government in accordance with the mandate in the 4th paragraph of the preamble to the 1945 Constitution of the Republic of Indonesia that its duty is to protect the entire Indonesian nation and all of Indonesia's blood as an embodiment of the 5th principle "Social Justice for All the People Indonesia". It regulates the Constitutional Court as the guardian of the constitution, as well as the executor of judicial power. If there is a law whose content is contrary to the constitution (unconstitutional), then the Court can cancel the existence of the law, either in its entirety or in parts of the law, by stating that it does not have binding legal force. The nature of the Constitutional Court's decision is final and binding. In this study the author focuses more on the nature of the Constitutional Court's decisions which are different from other decisions. This research aims to find ways so that the Constitutional Court's decisions can be reviewed like other decisions. This research aims to find ways so that the Constitutional Court's decisions can be reviewed like other decisions. By using a normative juridical approach and literature review.